Pore structure, gas storage and matrix transport characteristics of lacustrine Newark shale. (November 2018) - Fink, R.; Amann-Hildenbrand, A.; Bertier, P.; Littke, R.
Abstract: Shale gas production in the U.S. fuelled research activities in unconventional reservoir rock characterization. Most studies focused on organic-rich shales of marine origin, while disregarding lacustrine sequences. In this study, thirteen lacustrine shale samples from the Newark Basin, NJ, USA are comprehensively characterised in terms of pore structure, gas storage and matrix transport characteristics. These thermally overmature (VRr 1.4–2.7%) shales have a Na-rich, heterogeneous mineralogy with TOC contents of up to 3.6%. Methane sorption capacity and pore structure parameters as identified with low-pressure N2 physisorption (microporosity, BET surface area) are neither interrelated with each other nor with any shale components (e.g. clay content, TOC). In contrast, porosity shows a positive correlation with TOC content, which is also typical for many thermally overmature marine shale sequences. Correspondingly, porosity and TOC positively correlate to bedding parallel matrix permeability coefficients (between 2 and 80 nD at 40 MPa effective stress). In contrast, permeability coefficients perpendicular to bedding are two to three orders of magnitude lower. Compared to previous studies on marine lithotypes, Newark shales have rather poor gas storage properties with average He-porosities of 2.3% and average methane sorption capacities of 0.047 mmol g −1 . Highlights: Gas storage properties of lacustrine Newark shales are poor compared to marine shales. Newark shales have very low matrix permeabilities from subnD – 80 nD. Porosity is correlated to TOC. Newark shales have a heterogeneous and Na-rich mineralogy with low TOC contents.